2022
DOI: 10.1111/odi.14111
|View full text |Cite
|
Sign up to set email alerts
|

Direct relations between sense of coherence and oral health‐related quality of life in adolescents

Abstract: Oral health-related quality of life (OHRQoL) is defined as an important element for assessing the impact of oral disorders on the daily life of individuals (Sischo & Broder, 2011). Oral conditions, such as gingivitis and untreated dental caries, are prevalent in adolescents (World Health Organization, 2016) and associated with factors such as dental pain, eating discomfort, dissatisfaction, or embarrassment of the appearance of their teeth (Sun et al., 2018), negatively influencing OHRQoL. Conversely, not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Social support exerts a fundamental role during adolescence since it is related to other psychosocial factors, such as sense of coherence, self-management, and personal strength to deal with life problems [ 34 ]. These factors have a significant impact on oral health outcomes at this stage of life [ 35 , 36 , 37 ], where individuals experience biopsychosocial changes and emotional adaptations according to social structures [ 18 , 19 , 36 ]. Therefore, cognitive social capital seems to represent a relevant aspect of OHRQoL among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Social support exerts a fundamental role during adolescence since it is related to other psychosocial factors, such as sense of coherence, self-management, and personal strength to deal with life problems [ 34 ]. These factors have a significant impact on oral health outcomes at this stage of life [ 35 , 36 , 37 ], where individuals experience biopsychosocial changes and emotional adaptations according to social structures [ 18 , 19 , 36 ]. Therefore, cognitive social capital seems to represent a relevant aspect of OHRQoL among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Soares et al 8 showed that SoC did not influence OHRQoL in children; however, they found that the higher the SoC, the lower the impact on the family's quality of life at the age group from 7 to 15 years. The study by Tondolo Junior et al 9 evaluated subjects with a mean age of 17.5 years, and showed that SoC and dental caries had a direct effect on OHRQoL. The cohort study by Knorst et al 17 evaluated adolescents between 11-15 years of age, and showed that individuals with a high SoC were more likely to report better OHRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies carried out in adolescents also included those up to 15 years old. 8 The only study that includes individuals in late adolescence (from age 15 to 19 years) is the recent cohort study conducted by Tondolo Junior et al, 9 which has shown that SoC has a direct effect on the OHRQoL of adolescents with a mean age of 17.5 years.…”
Section: Introductionmentioning
confidence: 99%